Full-Length Transcriptome Sequencing and Comparative Transcriptomic Analysis Provide Insights Into the Ovarian Maturation of Exopalaemon carinicauda - Wang, Jiajia; Li, Jitao; Ge, Qianqian; Li, Wenyang; Li, Jian (Frontiers in Marine Science, 2022)
The ridgetail white shrimp Exopalaemon carinicauda has the potential to be used as a useful experimental organism in the field of crustacean research due to its transparent body, large egg, and short reproductive cycle. However, little is known about the regulatory mechanisms of ovarian maturation in E. carinicauda. In this study, we applied PacBio single-molecule long-read sequencing technology to unveil the whole transcriptome landscape of Exopalaemon carinicauda to better understand the molecular mechanisms of ovarian development. A total of 49.05 G polymerase read bases were generated, finally, 15, 151 unigenes were successfully identified with a mean length of 4, 257 bp and an N50 of 4, 884 bp from ovary tissues (five different ovarian developmental stages). A total of 14, 007 unigenes were successfully annotated in at least one public database. In addition, 8, 861 coding sequences, 4, 594 lncRNAs and 895 transcription factors were identified. Furthermore, we performed RNA-Seq analysis combined with Iso-Seq results to investigate ovarian maturation regulation mechanism and validated the results by quantitative real-time PCR. We annotated five vitellogenin isoforms in the full-length transcriptome, meanwhile these five genes and vitellogenin receptor suggested an important role during previtellogenesis of E. carinicauda. Genes were involved in PI3K-Akt signaling pathway, retinol metabolism, cell cycle and hedgehog signaling pathway, which showed obvious associations with ovarian maturation of E. carinicauda. We identified 40 DEGs, such as forkhead box protein L2, which may be related to ovarian development in the comparisons. The expression profiles of genes such as ecdysone receptor, ecdysone-induced protein 74EF, ecdysone inducible gene E75 and post-molt protein suggest that they were significantly associated with reproductive molting in the ovarian mature stage. In conclusion, the present study identified important genes and pathways involved in ovarian maturation, which might be useful for studying the reproductive regulation and mechanisms of ovarian maturation in E. carinicauda.